Paramedics As The First Line Of Defense: A Systematic Review Of Their Impact On Pre-Hospital Emergency Outcomes (The Review of Diabetic Studies, 2025)
Paramedics play a critical role as the first line of defense in emergency medical systems, delivering rapid, life-saving interventions in pre-hospital settings. This systematic review aims to evaluate the impact of paramedic-led care on pre-hospital emergency outcomes, including survival rates, response time, and clinical effectiveness. A structured search was conducted across major databases, including PubMed, Scopus, and Web of Science, following PRISMA guidelines. Eligible studies published between 2015 and 2025 were included based on predefined criteria focusing on paramedic interventions and measurable patient outcomes. The findings indicate that paramedics significantly improve patient survival, particularly in time-sensitive conditions such as cardiac arrest and trauma, through early assessment, rapid intervention, and advanced clinical decision-making. Moreover, reduced response times and the integration of advanced technologies further enhance pre-hospital care efficiency. Overall, paramedics are essential contributors to improving emergency care outcomes and healthcare system performance.